An Overview on LoRaWAN Technology Simulation Tools - Almuhaya, Mukarram A. M.; Jabbar, Waheb A.; Noorazliza, Sulaiman; A. H. A., Sulaiman (Springer, Cham, 2022)
Low-Power Wide Area Networks (LPWAN) technologies are playing a pivotal role in the IoT applications owing to their capability to meet the keys IoT requirements, i.e., long-range, low cost, small data volumes, massive devices number, and low energy consumption. The creation of new public and private LoRaWAN networks necessitates the use of avoiding node limits and collision prevention measures. Designers of IoT systems confront difficulty in determining the scalability of a given technology, with an emphasis on unlicensed frequency bandwidth (ISM) transmission in densely populated locations. However, picking the best simulation software might be a challenge. To provide a conceptual overview of seven LoRaWAN simulation tools, this paper outlines their key characteristics and the sorts of experiments they support. LoRaWAN simulators, resource utilization, and performance evaluation are all covered in-depth in this report. Furthermore, we classify and compare the most important simulation tools for investigating and analyzing LoRa/LoRaWAN network emulators that have been developed recently. This article will be used to help other researchers decide whether LoRaWAN simulation tool is best for their specific requirements.